A new species, Magnolia corquinensis, and a new record of Magnolia quetzal (Magnoliaceae) for Honduras - Morales-Molina, Sobeida; Vega-Rodríguez, Hermes; Shalisko, Viacheslav; Alemán-Avilez, Maryury; Vázquez-García, J. Antonio (Phytotaxa, 2024)
Magnolia corquinensis, M. sect. Magnolia (Magnoliaceae) is described and illustrated. A distribution map is provided. The species is critically endangered and endemic to Copán and Lempira, Honduras. It differs from M. celaquensis in many morphological features. In addition, Magnolia quetzal is recorded for the first for the flora of Honduras.